Extended health visibility in the hospital environment - Fernández-López, Helena (2009)
Wireless sensor networks can help healthcare providers enhance patient monitoring and communication capabilities. This paper describes the present state of the development of a vital signal monitoring network applied to the hospital environment. The proposed network is based on non-obstructive sensors able to communicate through a low power wireless sensor network based on the ZigBee protocol. This network enables continuous patient monitoring, creating entirely new mechanisms for providing healthcare under a plethora of cases (e.g. post-op, continuous care, and chronic diseases). The main advantages of this system include increased patient mobility, faster detection of potential problems, real-time feedback to caregivers and patients, and faster response to emergency situations.